Exploring Islamic spiritual ecology in Indonesia: Perspectives from Nahdlatul Ulama’s progressive intellectuals - Yakub, Muhammad (Journal for the Study of Spirituality, 2023)
This study aims to explore the ideas related to Islamic spiritual ecology in Indonesia as offered by Nahdlatul Ulama (NU), with a focus on three progressive intellectual subjects from NU: Roy Murtadho, Muhammad Al-Fayyadl, and Muhammad Jadul Maula. The study uses Michel Foucault’s concept of discourse and power and the genealogy method to examine historical statements by the three subjects and to reveal what is both said and unsaid. The research question driving the study is how these intellectuals offer Islamic spiritualism as an alternative basis in responding to contemporary ecological issues. The research findings indicate that: (1) Murtadho contends that economic liberalization enables exploitative practices of natural resources by extractive industries and ruling elites, contributing significantly to contemporary socio-ecological issues; (2) Al-Fayyadl’s concept of Cosmic Islam emphasizes the importance of religiosity and Islam in maintaining the order of the cosmos; (3) Maula mentions that the idea of caring for nature and mitigating ecological disasters has actually become a part of the spiritual practice of religious communities in Indonesia. Overall, the study reveals the potential for Islamic spiritualism to offer unique perspectives on ecological issues in Indonesia.